A year of Covid-19: experiences and lessons learnt by small European island states—Cyprus, Iceland and Malta. (3rd January 2022) - Cuschieri, Sarah; Pallari, Elena; Hatziyianni, Amalia; Sigurvinsdottir, Rannveig; Sigfusdottir, Inga Dora; Sigurðardóttir, Árún Kristín
Abstract: Background: COVID-19 became a global pandemic within weeks, as every country including small states and islands experienced a surge in cases. Small islands are known to face several challenges in the quest to curb the viral spread, but with the absence of land boarders and small population size, these factors should have played to their advantage to minimize the spread. The aim of this article was to compare and contrast the COVID-19 situation, restrictions, preparedness, management and the healthcare systems between the small population island states of Cyprus, Iceland and Malta. Methods: Data were obtained from Ministry of Health websites and COVID dashboards of the three respective Island states in Europe. Comparisons were made between the reported cases, deaths, excess deaths, years of life lost, swabbing rates, restrictive measures, vaccination roll-out and healthcare system structures. Results: Cyprus and Malta contained the COVID-19 spread better than Iceland during the first wave. However, a significantly higher viral spread and mortality rates were observed in Malta during the second waves. Similar healthcare preparedness and services, restrictions and relaxation measures were implemented across the three islands with some exceptions. Covid-19 vaccination has initiated across all Islands with Malta leading the vaccination roll-out. Conclusion: The small population size and island status proved to be an asset during the first wave of COVID-19, but different governance approaches led to a different COVID-19 outcomes, including high mortality rates during the transition phases and the subsequent waves.